P848 FXR -1G>T (rs56163822) predicts deleterious outcomes in Crohn's disease. (16th January 2018) - Wilson, A; Teft, W; Al-Mousa, A; Kim, R
Abstract: Background: Crohn's disease (CD) pathogenesis is multi-factorial. Bile acids as well as the bile acid-activated nuclear receptor, farnesoid X receptor (FXR) regulate several processes, including intestinal epithelial integrity, that appear to be defective in CD and contribute to disease manifestation. In humans and mice, FXR deficiency appears to portend a more severe disease phenotype in the setting of a primary insult. The novel genetic variant FXR-1G>T may decrease FXR activity. The fibroblast growth factor (FGF) 19 is a downstream product of FXR activity and is thus used as a surrogate marker. We hypothesise that changes in the intestinal barrier regulated through alterations in FXR activity may contribute to a more severe CD phenotype including a more rapid progression to surgery. We aim to determine whether the FXR-1T variant allele is a predictor of disease severity in CD. Furthermore, we hope to suggest a molecular mechanism by which genetic variation in FXR may contribute to outcomes of severity in CD. Methods: The presence of the genetic variant FXR-1G>T was evaluated in 386 individuals with CD using real-time polymerase chain reaction (PCR) technique. FGF19 plasma concentrations were evaluated in a subset of CD individuals ( n = 137) who underwent a CD-related intra-abdominal surgical intervention using an enzyme-linked immunosorbent assay (ELISA). FXR-1G>T variant status and FGF19 plasma concentrations were evaluated in relation to one another as well as to important clinical outcomes related to CD severity including risk of and time to surgery, failure of drug therapy, number of flares and number of hospitalisations. Results: There was a strong association between carriers of the variant T allele and surgical intervention (odds ratio, OR=2.80, 95% CI=1.16–6.72, p = 0.02). Moreover, FXR-1T variant carriers were more likely to go on to an early surgical intervention compared with wild-type individuals (5.99 years ± 6.94 vs. 1.56 years ± 2.08; hazard ratio, HR=5.433 (2.186–13.51), p < 0.001). FXR -1T remained an independent predictor of early progression to surgical intervention in CD in a multiple linear regression model adjusting for age, sex, weight, drug exposure and other surgical risk factors. FGF19 plasma concentrations were lower in FXR-1GT variant carriers, though this did not achieve statistical significance on univariate analysis or multivariate analysis (GG = 0.35 pg/l ± 0.04 pg/l; GT = 0.23 pg/l ± 0.05 pg/l, p = 0.094). Conclusions: Screening CD patients for FXR-1T variant carrier status may be useful for identifying patients at risk for early, poor outcomes. Carriers of the variant allele may benefit from earlier, more aggressive medical management.